Cultural Variations on Gender: Latin American Marianismo/Machismo in Australia - Moraes-Gorecki, Vanda (The Australian journal of anthropology, 1988)
This paper concerns cultural and social ideas and practices on gender differences among Latin American immigrants in Australia. It explores the ways in which immigrants' notions of gender relations expressed as marianismo/machismo generated in their societies of origin, influence the social gender relationships among the settlers in Australia. The argument is that marianismo/machismo are ideological constructs which reinforce woman's oppression and at the same time help to perpetuate social relations of inequality between men and women.